CTRP11 contributes modestly to systemic metabolism and energy balance. Issue 6 (17th May 2022) - Sarver, Dylan C.; Xu, Cheng; Carreno, Dana; Arking, Alexander; Terrillion, Chantelle E.; Aja, Susan; Wong, G. William
Abstract: C1q/TNF‐related proteins (CTRP1‐15) constitute a conserved group of secreted proteins of the C1q family with diverse functions. In vitro studies have shown that CTRP11/C1QL4 can inhibit adipogenesis, antagonize myoblast fusion, and promote testosterone synthesis and secretion. Whether CTRP11 is required for these processes in vivo remains unknown. Here, we show that knockout (KO) mice lacking CTRP11 have normal skeletal muscle mass and function, and testosterone level, suggesting that CTRP11 is dispensable for skeletal muscle development and testosterone production. We focused our analysis on whether this nutrient‐responsive secreted protein plays a role in controlling sugar and fat metabolism. At baseline when mice are fed a standard chow, CTRP11 deficiency affects metabolic parameters in a sexually dimorphic manner. Only Ctrp11 ‐KO female mice have significantly higher fasting serum ketones and reduced physical activity. In the refeeding phase following food withdrawal, Ctrp11 ‐KO female mice have reduced food intake and increased metabolic rate and energy expenditure, highlighting CTRP11's role in fasting–refeeding response. When challenged with a high‐fat diet to induce obesity and metabolic dysfunction, CTRP11 deficiency modestly exacerbates obesity‐induced glucose intolerance, with more pronounced effects seen in Ctrp11 ‐KO male mice. Switching to a low‐fat diet after obesity induction results in greater fat loss in wild type relative to KO male mice, suggesting impaired response to obesity reversal and reduced metabolic flexibility in the absence of CTRP11. Collectively, our data provide genetic evidence for novel sex‐dependent metabolic regulation by CTRP11, but note the overall modest contribution of CTRP11 to systemic energy homeostasis.